Imperatives for Effective Monitoring and Evaluation System of Community Based Rural Development Projects (A Case of Interim Impact Study) - Kasi, Anwar Saleem; Khan, Abdul Rahit (Economic Journal of Nepal, 2002)
Available with Full text.